CLINICAL EFFICACY OF VACUUM-ASSISTED THERAPY IN THE TREATMENT OF PULMONARY ABSCESSES IN PATIENTS WITH DIABE-TES MELLITUS - Khamdamov, Sh.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background: Pulmonary abscess remains a severe complication in diabetic patients, often associated with protracted healing, high surgical risk, and prolonged hospitalization. Negative pressure (VAC) therapy has shown promise in accelerating infection control and tissue repair, yet its application in thoracic surgery remains limited. Objective: To evaluate the clinical effectiveness of vacuum-assisted closure therapy in the treatment of pulmonary abscesses in patients with type 2 diabetes mellitus. Materials and Methods: A prospective controlled study included 74 patients with pulmonary abscesses and type 2 diabetes. The main group (n=38) received surgical drainage followed by VAC therapy; the control group (n=36) received standard drainage without negative pressure. Key endpoints included duration of drainage, wound healing time, length of hospital stay, and rate of complications and mortality. Results: The VAC group demonstrated significantly shorter drainage duration (6.2±1.1 vs. 9.4±1.3 days; p<0.01), faster cavity closure (11.6±1.9 vs. 17.2±2.3 days; p<0.001), and reduced hospitalization (13.8±2.4 vs. 20.6±3.2 days; p<0.001). The complication rate was lower in the VAC group (10.5% vs. 27.8%), and no mortality was observed, compared to 2 deaths in the control group. Conclusion: VAC therapy in diabetic patients with pulmonary abscesses significantly improves healing dynamics and reduces postoperative complications. This method is an effective adjunct to surgical drainage and may be considered for broader use in thoracic surgery.